Socialization Regarding Negative Impacts of Use Gadgets for Al-Washliyah Berastagi Private Elementary School Students - Hanna Niken J Sihotang; Ratna Wahyuni; Yunistita; Egidia P; Dinda S; Resaloista T (Indonesian Journal of Society Development, 2023)
Gadgets are media that are used as modern communication tools. Now communication activities have developed increasingly more advanced with the emergence of gadgets. Gadgets have an impact on early childhood social development. Excessive use of gadgets will have a negative impact on children's social and emotional development. The negative effects of using gadgets on children include children becoming closed personalities, sleep disturbances, being alone, violent behavior, fading creativity, and threats of cyberbullying. With the results of this socialization activity, it provides education to service participants, namely Al-Washliyah Berastagi Private Elementary School students so that they can minimize the negative impact of using gadgets